Variability of Aerosols and Clouds Over North Indian and Myanmar During the COVID-19 Lockdown Period - Divyaja Lawand; Sudheer Bhakare; Suvarna Fadnavis; Rohini L. Bhawar; P. R. C. Rahul; Pradeep Kumar Pallath; Simone Lolli (Frontiers in Environmental Science, 2022)
The implementation of a nationwide lockdown to curb the spread of COVID-19 disease has reduced the loading of anthropogenic aerosols. However, AOD distribution over South Asia during the lockdown period shows a dipole pattern: reduction over North Indian and enhancement over the Myanmar region. This dipole pattern is evident in some datasets (MODIS, MERRA, and CALIPSO). MODIS fire counts collocated with CALIPSO smoke aerosols show enhancement over Myanmar indicating the contribution from fires. However, over the North India region number of fires during the lockdown period are less compared to climatology. Thus, the observed reduction in AOD is due to fires and anthropogenic sources. Our analysis shows that aerosols originating from biomass burning forms a layer (900–600 hPa) over the Myanmar region that produces atmospheric heating (0–2.8 K/day) that eventually leads to cloud dissipation/burning (negative in-atmospheric cloud radiative forcing ∼ −13 W/m2) and precipitation reduction (−1 to −4 mm) over Myanmar. In contrast, the aerosol reduction over North India favors cloud formation, that is, increase in cloud cover and reduction in specific cloud liquid water content leading to precipitation enhancement, indicating the anti-Twomey effect.